Influence of sulfentrazone and metribuzin applied preemergence on soybean development and yield. (1st April 2021) - Arsenijevic, Nikola; de Avellar, Matheus; Butts, Liberty; Arneson, Nicholas John; Werle, Rodrigo
Abstract: The use of photosystem II (PSII)-inhibitor and/or protoporphyrinogen oxidase (PPO)-inhibitor PRE herbicides in soybean may, under adverse environmental conditions, result in early season crop injury. A field study was conducted near Brule and North Platte, Nebraska, during the 2016 and 2017 growing seasons with the objective to evaluate the impact of PRE herbicides metribuzin (PSII-inhibitor) and sulfentrazone (PPO-inhibitor) on early season soybean development, final plant stand, and yield using 22 soybean varieties adapted to southwestern Nebraska. Herbicide treatments consisted of metribuzin (560 g ai ha −1 ) and sulfentrazone (280 g ai ha −1 ) applied within 3 d after planting and a nontreated control (NTC). Sulfentrazone reduced green canopy vegetation at the V2 growth stage by 22% and final plant stand at physiological maturity by 10% compared with the NTC. The number of pods per plant was 16% higher for sulfentrazone and the number of seeds per plant was 15% and 4% higher for sulfentrazone and metribuzin compared with the NTC, respectively. Sulfentrazone and metribuzin resulted in a slightly higher yield (3%) compared with the NTC, thus no yield reduction from PRE herbicides was observed in this study. These results support other findings that sulfentrazone and metribuzin have potential to cause early-season crop injury; however, when applied according to their label recommendations and following regional agronomic management practices, this impact may not translate into soybean yield reduction while such herbicides provide effective soil residual weed control.